Digital Teacher Competence Levels in Elementary Schools on Learning and Knowledge Technologies (LKT) - Romero-Argueta, Jesús; Cortez, Brenda Guadalupe; Carranza-Cortez, Lorena Lisseth; Argueta-Amaya, Lorena de Los Ángeles (International Journal of Education, Management, and Technology, 2025)
This study examines the digital competency levels of elementary school teachers in Tecapán, El Salvador, with a focus on their ability to effectively utilize learning and knowledge technologies (LKT) in line with the Common Framework for Teacher Digital Competence (CFTDC). Employing a descriptive research design, data were gathered from a sample of 47 participants, including teachers, principals, and vice principals, using a 21-item online questionnaire. The instrument assessed five core dimensions of digital competence: information and data literacy, communication and collaboration, digital content creation, safety, and problem-solving. Results indicate that 72.2% of respondents demonstrate an intermediate level of digital competence. Notable strengths were observed in communication and collaboration (mean = 13.28), while significant weaknesses were identified in information and data literacy (mean = 6.49). Based on these findings, the study recommends targeted professional development initiatives to address identified gaps, particularly in data literacy and critical information handling. Enhancing teachers’ digital proficiency is essential to promoting equitable access and effective integration of educational technology in elementary learning environments.